A Signal-Interpreted Approach to the Supervisory Control Theory – Extension to Partially Controllable Signals. Issue 7 (2018) - Desgeorges, Loïc; Provost, Julien
Abstract: After highlighting the difficulties encountered while implementing a supervisor on actual industrial controllers and different approaches already suggested to tackle them, this paper presents a signal-interpreted approach to the Supervisory Control Theory (SCT) framework. This work focuses on further developments of this approach for reactive systems. Due to fundamental differences between event- and signal-based approaches, new algorithms have to be implemented to apply an SCT approach on the basis of signal-interpreted Boolean finite automata extended with variables. Also, compared to a previous version of this approach, partially controllable signals are introduced.